Data Visualization. - Mallon, Melissa (Public Services Quarterly)
The article reviews data visualization designing and mapping tools and soft wares including Map box by MapBox LLC, Creately by Cinergix Pty. Ltd and Gliffy Online by Gliffy Inc.